The Development of a Mental Toughness Scale for Doctors: A Psychometric Study - Aslam, Saba; Saleem, Sadia; Mahmood, Zahid (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To develop a scale of mental toughness among medical doctors. METHODOLOGY: In the current study Mixed-Method research design was used, qualitative design was used to elicit the items for mental toughness and quantitative was used to establish psychometrics. This study was carried out in Govt. hospitals of Lahore. The study was carried out from August 2018-April 2019. The construct of mental toughness was explored from 20 post graduate residents and house officers (10 men and 10 women) through a semi structured interview. After excluding the repetition finalist of 40 items was further validated by 10 experts and based on the 50% agreement from the experts, a list of 30 items was finalized and piloted on 40 doctors (20 men and 20 women) for assessing user friendliness. Finally, a sample of two hundred doctors (100 men and 100 Women) between the ages of 22 to 36 (M =26.17, SD =1.83) from different Government. Hospitals of Lahore were given Mental Toughness Scale, Depression, Anxiety, Stress Scale (DASS-21) along with a Demographic form. RESULTS: Exploratory factor analysis through varimax rotation yielded three factors solution named as Determination, Resilience and Optimism. The MTS was found to have sound psychometric properties as split half reliability was .74 test, retest reliability was .75. CONCLUSION: Mental toughness scale was found high psychometric properties; results were discussed in term of counseling and enhancing positive strengths in medical doctors.